Determinants of human development: Capturing the role of institutions - Michael Binder; Georgios Georgiadis (Center for Economic Studies and ifo Institute (CESifo), 2011)
In this paper, we study development in a panel of 87 countries from 1970 to 2005. We focus on characterizing institutionally driven heterogeneities in the development effects of macroeconomic policies and on comparing the development process as measured by GDP to that measured by the Human Development Index (HDI). We do so within a novel dynamic panel modelling framework that can account for crucial aspects of both the cross-sectional and intertemporal features of the observed process of development, and that can capture the dependence of the development effects of macroeconomic policies on differences in countries' persistent characteristics, such as their institutions. Among our findings are that macroeconomic policies affect development with less delay than suggested by conventional econometric frameworks, yet impact HDI with longer delay and overall less strongly than GDP. Differences in countries' persistent characteristics may even affect the sign of the long-run development effects of a given macroeconomic policy: Fiscal stimuli in the form of government consumption expansions positively affect long-run GDP in countries with low institutional quality, but negatively affect long-run GDP in countries with high institutional quality.
Keywords: C23; O10; 330; human development; institutions; dynamic panel modelling; Sozialer Indikator; Entwicklung; Institutionalismus; Wirtschaftspolitik; Panel; Schätzung; Welt